Impact of Health Education about Stroke Pre-Hospital Emergency Treatment on Family Knowledge in Puskesmas Kartini Pematangsiantar Region - Siregar, Nabilah; Damanik, Derma Wani; Handayani, Astika (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2023)
Introduction: Stroke was the second leading cause of death in the world from 2000 to 2019, reached 11% of total deaths. Delay in pre-hospital treatment of stroke patients can lead to a reduced proportion of patients receiving recanalization therapy. Lack of family knowledge can cause families to seek help late when an attack occurs, the severity of the disease, repeated strokes even to death. Objective: This study aims to determine the effect of health education about pre-hospital stroke management on the knowledge of families of stroke sufferers in the area of ?? Kartini Public Health Center, Pematangsiantar City. Method: The research sample were 40 family members of stroke sufferers. The sampling technique was purposive sampling. Data analy used the Wilcoxon test. Result: The results showed that majority of respondents before receiving health education had less knowledge as many as 22 people (55%), and majority of respondents had good knowledge as many as 29 people (72.5%) after being given health education, and there was an influence of health education about stroke pre-hospital management on the knowledge of families of stroke sufferers (p value 0.000). Conclusion: Health education can increase family knowledge.